The Influence Of Financial And Non-Financial Rewards On Employees Organizational Commitment At Pt Alindra - Riesta Martha Melisa; Yuningsih (Cita konsultindo, 2025)
This study aims to analyze the influence of financial and non-financial rewards separately on organizational commitment among employees at PT Alindra, a labor provider company for PLTU MT Sumbagsel 1 in Baturaja. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 100 permanent employees who had worked for at least six months. The sampling technique used was census. Validity and reliability tests were conducted using Confirmatory Factor Analysis and Cronbach’s Alpha. The data were analyzed using simple linear regression and t-test with the help of SPSS. The results showed that financial rewards have a positive and significant effect on employees’ organizational commitment, and non-financial rewards also have a positive and significant effect. These findings highlight the importance of implementing a balanced and sustainable reward system to enhance employee loyalty and organizational commitment.